Study of hospitalization and mortality in Korean diabetic patients using the diabetes complications severity index - Yoo, Hyunju; Choo, Eunjung; Lee, Sukhyang (BMC Endocrine Disorders, 2020)
Background: The prevalence of type 2 diabetes mellitus (T2DM) is expected to increase from 7.7% in 2017 to 8.4% in 2045 worldwide. Diabetes complications contribute to morbidity and mortality. To evaluate whether the diabetes complications severity index (DCSI) was associated with increased risks of mortality and hospitalization. Methods: A retrospective cohort study was conducted using the National Health Insurance Database (NHID) sample cohort of 1,102,047 patients (2002-2015) in Korea. Diabetes complications were evaluated at 2 years after the initial diagnosis and during the subsequent follow-up period (mean duration 6.56 ± 2.81 years). The type and severity of complications were evaluated on the basis of the International Classification of Disease Ninth (ICD-9) codes used in DCSI with 7 categories and 55 subcategories of complications. The Cox proportional hazard and Poisson regression models were used to evaluate the mortality and hospitalization rates. The incidence and relative risk of diabetes complications as well as the risk of mortality and hospitalization were the main outcome measures. Results: A total of 27,871 patients were finally included and grouped by the number of complications present at 2 years. Four hundred ninety patients (5.37%) died without complications, 659 (7.31%) died with one complication and 1153 (11.85%) died with two or more complications. As DCSI at index date increased, the risk of additional new diabetes complications increased by 26% [relative risk (RR) 1.26, 95% CI 1.25-1.27]. The risks of mortality and hospitalization were linearly related to DCSI [hazard ratio 1.13 (95% CI 1.11-1.16), relative risk 1.04 (95% CI 1.03-1.06)]. Conclusions: Patients with higher incidence and severity of diabetes complications have increased risks of mortality and hospitalization.
Keywords: Aged; Cause of Death; Cohort Studies; Databases, Factual; Diabetes Complications; Diabetes Mellitus, Type 2; Female; Hospitalization; Humans; Incidence; Male; Middle Aged; Mortality; Republic of Korea; Retrospective Studies; Severity of Illness Index; Diabetes complications; Diabetes mellitus; Korea; National Health Insurance Database